2016
DOI: 10.1177/1077695816650324
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Study of Student Experiences in a Multiplatform Journalism Course

Abstract: Studies suggest that the goal of convergence curriculum should be one in which students are prepared both conceptually and practically. The purpose of this study was to examine the experience of students working with new and traditional technologies to develop and produce news stories. The results indicate that participation in the course strengthened both students’ technological skills and skills of importance in traditional journalism—the ability to write, interview, and listen well; to construct a news stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…Auger, Tanes-Ehle, and Gee (2017) acknowledged that the goal of a journalism curriculum should be one in which students are prepared both conceptually and practically. They studied the experience of students working with new and traditional technologies to develop and produce news stories and found that the students’ technological and traditional skills were both stronger when practiced in tandem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Auger, Tanes-Ehle, and Gee (2017) acknowledged that the goal of a journalism curriculum should be one in which students are prepared both conceptually and practically. They studied the experience of students working with new and traditional technologies to develop and produce news stories and found that the students’ technological and traditional skills were both stronger when practiced in tandem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The case study of my class, Truth, Lies, and Accuracy in the Digital Age applied PBL and media literacy pedagogies and theories into the classroom using current media texts that are part of the post-truth era. Especially in a time of increased information disorder (Wardle & Derakhshan, 2017), it is crucial to find methods and texts that can engage undergraduate students who will become part of the media industry (Auger et al, 2017). This pedagogy allows journalism and media educators to broaden the learning to be able to see the economics, power relations, and ideology beyond merely focusing on verification and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Having journalism students unaware of how media news operates in "real life" can be addressed by a reciprocal process with various stakeholders (Gutsche, Jacobson, Pinto, & Michel, 2017). This is why it is important to add a project-based learning (PBL) activity to produce media as an engaged journalism process, while also analyzing and evaluating narratives that enhance journalism skills such as writing and listening well, constructing a story, and adapting narratives to various situations (Auger, Tanes-Ehle, & Gee, 2017). Brooks and Ward (2007) showed that using media technologies in the classroom helped to synthesize multiple pedagogies and make participants more engaged, which enhanced students' ability to analyze media representations of diversity, especially regarding gender and race.…”
Section: Why Media Literacy Educationmentioning
confidence: 99%
“…While social media tools have their downsides, this study reveals how students can leverage and build their strengths to interact, collaborate, and create a dialogue with an audience in an appropriate manner (Auger, Tanes-Ehle & Gee 2017;Patrão & Figueiredo 2011;Hermida 2010).…”
Section: (Fgd4 Participant)mentioning
confidence: 93%